The Influence of Semantic Processing on Phonological Decisions in Children and Adults: A Magnetoencephalography (MEG) Study. - Wehner, Daniel T.; Ahlfors, Seppo P.; Mody, Maria (Journal of Speech, Language & Hearing Research, 2007)
Purpose: To examine the behavioral effects and neural activation patterns associated with implicit semantic processing influences on phonological judgments during reading in children and adults. Method: Whole-head magnetoencephalography (MEG) recordings were obtained from 2 groups, children (9-13 years) and adults, performing a homophone judgment task. The stimuli consisted of pairs of sequentially presented written words that were either homophones, synonym foils, or unrelated control words. Results: The difference in the time taken to respond to synonym pairs relative to control pairs of stimuli, called the semantic interference effect (SIE), was, on average, 24 ms for adults and 86 ms for children. Source analysis of the MEG data using minimum-norm estimation (MNE) yielded less activation in the adults for the synonym condition compared with the control condition in right anterior temporal and inferior frontal cortex 300-500 ms after the onset of the 2nd word in a pair, suggestive of semantic priming as well as inhibition of the SIE. A similar priming effect was observed for the children in left-anterior temporal cortex. Conclusion: The observed group differences in the magnitude of the SIE and brain activation patterns may reflect developmental differences in the effects of semantic information on phonological decisions during word processing. Reprinted by permission of the publisher.